2005
DOI: 10.1107/s1600536805031557
|View full text |Cite
|
Sign up to set email alerts
|

N-(4-Methoxyphenyl)-2-(quinolin-8-yloxy)acetamide monohydrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.003 Å R factor = 0.032 wR factor = 0.083 Data-to-parameter ratio = 8.4For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…All bond lengths and angles are within normal ranges (Allen et al, 1987) and are comparable to those in the related compound, N-(4-methoxyphenyl)-2-(quinolin-8-yloxy)acetamide monohydrate, (II) (Wen et al, 2005). The non-H atoms in (I) show a nearly planar conformation, with a dihedral angle of 4.03 (1) between the benzene ring and the quinoline moiety, while the corresponding value in (II) is 67.06 (7) .…”
supporting
confidence: 57%
“…All bond lengths and angles are within normal ranges (Allen et al, 1987) and are comparable to those in the related compound, N-(4-methoxyphenyl)-2-(quinolin-8-yloxy)acetamide monohydrate, (II) (Wen et al, 2005). The non-H atoms in (I) show a nearly planar conformation, with a dihedral angle of 4.03 (1) between the benzene ring and the quinoline moiety, while the corresponding value in (II) is 67.06 (7) .…”
supporting
confidence: 57%
“…As part of our studies on amide compounds, the title compound, (I), was synthesized and the structure was determined. The bond lengths (Table 1) are comparable with those in the related compound, N-(4-methoxyphenyl)-2-(quinolin-8yloxy)acetamide monohydrate, (II) (Wen et al, 2005). The non-H atoms in (I) show a nearly planar conformation, with a dihedral angle of 8.46 (6) between the benzene ring and the quinoline moiety, while the corresponding value in (II) is 67.06 (7) .…”
supporting
confidence: 55%
“…The title compound was prepared according to the literature method of Wen et al (2005). Colorless single crystals suitable for X-ray diffraction were obtained by slow evaporation of a petroleum etherethyl acetate (1:3, v/v) solution over 5 d.…”
Section: Methodsmentioning
confidence: 99%
“…All bond lengths and angles in (I) are normal (Allen et al, 1987) and comparable with those in a related compound (Wen et al, 2005). The molecules are linked by intermolecular hydrogen bonds, with N and O atoms acting as donors and acceptors (Table 1, Fig.…”
Section: Commentmentioning
confidence: 70%
“…In our ongoing studies of amide-type acyclic compounds with 8-hydroxyquinolinate as the skeleton (Wen et al, 2005), the title compound has been synthesized and its structure is reported here.…”
Section: Commentmentioning
confidence: 99%